Pelapisan Gel Aloe Vera (Aloe barbadensis Miller) dan Ekstrak Jahe pada Buah Tomat (Lycopersicum esculentum Mill) - Ni Wayan Prilia Dewi; Ida Ayu Rina Pratiwi Pudja; Pande Ketut Diah Kencana (Jurnal BETA (Biosistem dan Teknik Pertanian), 2021)
Tomato fruit (Lycopersicum esculentum Mill) is a horticultural plant is well utilized as fresh fruit, vegetables and daily cooking spices, tomato plants are shrubs, both planted in the lowlands and highlands. Tomatoes have perishable properties due to improper handling of tomatoes before, during and after harvesting resulting in a decrease in quality. The purpose of this study was to maintain the shelf life of tomatoes with the best concentration of aloe vera gel and ginger extract in cold storage. This study uses a factorial completely randomized design (CRD) consisting of two factors. The first factor is the concentration of aloe vera gel and the second factor is the concentration of ginger extract. The first factor consists of three levels, namely: 0% aloe vera gel, 30% aloe vera gel, 50% aloe vera gel and added control. The second factor consists of 2 levels, namely: 8% ginger extract, 10% ginger extract and added control and stored at a showcase temperature of 10±2°C. Each treatment was repeated 3 times, with storage for 25 days. The parameters observed in this study are: repiration rate, vitamin C, hardness, level of damage and organoleptics. The best results showed in the treatment of 30% aloe vera gel and 8% ginger extract with a respiration rate parameter value of 40.26 ml CO2/Kg. Hours, vitamin C with a value of 27.63 mg/100g, hardness with a value of 3.53 kg/cm, damage level with a value of 3.56 and organoleptic the scent with a value of 3.62.